2022
DOI: 10.1186/s12909-022-03213-0
|View full text |Cite
|
Sign up to set email alerts
|

Overcoming language barriers, enhancing collaboration with interpreters – an interprofessional learning intervention (Interpret2Improve)

Abstract: Background Language barriers (LB) are common in patient care. They can negatively impact the quality of care, and increase costs. LB can be overcome by using interpreters. However, collaboration with interpreters is a professional activity which can and needs to be learnt. Interpret2Improve is an innovative educational intervention where medical and nursing students learn together how to address LB and effectively collaborate with interpreters. Methods … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…27 This highlights the importance of having access to interpreters and understanding how to effectively work with them to ensure accurate communication and understanding between healthcare practitioners and patients who do not speak a shared language. 18 28 A previous study found that using professional interpreters who were present at the location was a frequently suggested solution for overcoming language barriers in healthcare settings. [27][28][29] However, the use of professional interpreters may vary by the type of healthcare professional and clinical situation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 This highlights the importance of having access to interpreters and understanding how to effectively work with them to ensure accurate communication and understanding between healthcare practitioners and patients who do not speak a shared language. 18 28 A previous study found that using professional interpreters who were present at the location was a frequently suggested solution for overcoming language barriers in healthcare settings. [27][28][29] However, the use of professional interpreters may vary by the type of healthcare professional and clinical situation.…”
Section: Discussionmentioning
confidence: 99%
“…18 28 A previous study found that using professional interpreters who were present at the location was a frequently suggested solution for overcoming language barriers in healthcare settings. [27][28][29] However, the use of professional interpreters may vary by the type of healthcare professional and clinical situation. 27 29 Participants occasionally relied on patients' family members or bilingual staff as interpreters, even though they may lack proficiency in medical terminology, potentially side-lining professional interpreters.…”
Section: Discussionmentioning
confidence: 99%
“…This study explores the influence of teachers' age on implementing CPBL when teaching English as a Foreign Language (EFL) and determines teachers' perceptions, views and attitudes Regarding this methodology. Krampe et al (2022) Te aim of this study was to evaluate the feasibility of the collaborative learning module and to evaluate its effect from the learners' perspectives.…”
Section: Screeningmentioning
confidence: 99%
“…The samples included students, teachers, and children of all ages. However, 16 studies found in favour of students (López Oterino, 2022;Panhwar & Melanie, 2022;Flynn et al, 2022); Namusoke & Rukundo, 2022;Krampe et al, 2022;Liu et al, 2022;Angeliki, 2022;Markoglou and Angeliki, 2022); Lázaro-Carrascosa et al, 2021;Carmona-Medeiro and Cardeñoso Domingo, 2021;Martín et al, 2020;Kadam & Sawant, 2020;Balbay, 2019;Dominique et. al., 2018;Ward et al, 2017;Gachago et al, 2011).…”
Section: Type Of Samplesmentioning
confidence: 99%
See 1 more Smart Citation